A benchmark system to investigate the non-minimum phase behaviour of multi-input multi-output systems. Issue 3 (3rd July 2018) - Tofighi, SaeedReza; Merrikh-Bayat, Farshad
Abstract: In this paper, the problem of designing a multi-input multi-output (MIMO) system for studying the non-minimum phase (NMP) behaviour is considered. For this purpose, a NMP MIMO circuit is proposed and studied under different conditions. The main reason for designing this circuit is the lack of a simple and flexible benchmark for examining different control methods. Due to the simple structure and capability of showing different NMP characteristics, our proposed system is a suitable choice to study the behaviour of these systems. Also, our proposed system can be extended by series and parallel connections to generate more complicated benchmarks. The other advantages of this system are the large number of tunable parameters, adjustable interaction, variable number of poles and zeros, and inexpensive cost. Moreover, this benchmark can be used as a tool for hardware simulation. Finally, an optimal decoupling control is applied to this benchmark to verify its effectiveness.